Parasites infestation on juvenile tiger grouper (Epinephelus fuscoguttatus) nursed in net cage at Sea Farming Instalation Kepulauan Seribu, Jakarta - Hadiroseyani, Yani; Effendi, Irzal; Rahayu, Agnis Murti; Arianty, Heni Sela (Indonesian Society of Scientific Aquaculture (ISSA), 2010)
This study was aimed to identify fauna parasite of juvenile tiger grouper (Epinephelus fuscoguttatus) on the two locations of floating net at Floating Net Sea Farming Center, Pulau Seribu Jakarta. A total of five tiger grouper fry from each location, checked every two weeks during the nursery period in August-September 2008 and June-August 2009. Parasites of young tiger grouper found were protozoa (Trichodina and myxosporea), monogenea Diplectanum, metaserkaria digenea, and isopods Alitropus. Diplectanum infestation was dominant with prevalence reached 100% and the average intensity of 2,87-72,8. Fish nursed in the Perairan Pulau Semak Daun was more susceptible compared to the fish nursed in Pulau Karang Congkak. Keywords: tiger grouper, parasite, infestation, Seribu Island. ABSTRAKPenelitian ini bertujuan untuk mengidentifikasi penyakit yang menyerang benih kerapu macan pada masa pendederan dalam karamba jaring apung di dua lokasi Karamba Jaring Apung Balai Sea Farming, Kepulauan Seribu, yaitu di Perairan Pulau Semak Daun dan Perairan Pulau Karang Congkak. Sebanyak 5 ekor benih kerapu macan dari masing-masing lokasi, diperiksa setiap minggu selama dua periode pendederan pada bulan Agustus-September 2008 dan bulan Juni-Agustus 2009. Fauna parasit benih kerapu macan pada masa pendederan dalam jaring apung tersebut meliputi protozoa (Trichodina dan myxosporea), monogenea Diplectanum, metaserkaria digenea, dan isopoda Alitropus. Diplectanum merupakan parasit yang mendominasi dengan prevalensi mencapai 100% dan intensitas rerata 2.87–72,8. Pada Perairan Pulau Semak Daun lebih banyak ditemukan jenis parasit dengan prevalensi dan intensitas yang cukup tinggi dibandingkan dengan Perairan Pulau Karang Congkak.Kata kunci: ikan kerapu macan, parasit, infestasi, Pulau Seribu.